A Morphological Approach to the Diagnosis of Protozoal Infections of the Central Nervous System. (14th July 2011) - Chimelli, Leila
Abstract : Protozoal infections, though endemic to certain regions, can be seen all around the world, because of the increase in travel and migration. In addition, immunosuppression associated with various conditions, particularly with HIV infection, favors the occurrence of more severe manifestations and failure to respond to treatments. The CNS may be the only affected system; when not, it is often the most severely affected. Despite information obtained from clinical, laboratory, and imaging procedures that help to narrow the differential diagnosis of intracranial infections, there are cases that need confirmation with biopsy or autopsy. Predominant presentations are meningoencephalitis (trypanosomiasis), encephalopathy (cerebral malaria), or as single or multiple pseudotumoral enhancing lesions (toxoplasmosis, reactivated Chagas' disease). The immune reconstitution disease, resulting from enhancement of pathogen-specific immune responses after HAART, has altered the typical presentation of toxoplasmosis and microsporidiosis. In this paper, a morphological approach for the diagnosis of protozoal infections affecting the CNS (amoebiasis, cerebral malaria, toxoplasmosis, trypanosomiasis, and microsporidiosis) is presented.